Dari Protes Menuju Kekacauan: Sosiologi Visual dan Kriminologi Visual Pembakaran DPRD Makassar dalam Liputan Kompas - Hadisaputra; Sri Wahyuni; Rahmadani Islawiyah; Risqa Ayu Ramadani; Ilham Darmawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Political protests increasingly occur in hybrid arenas where street interactions and media visibility combine to produce collective meaning. This study examines how Kompas's visual coverage of the 2025 burning of the Makassar Regional People's Representative Council (DPRD) building constructed spontaneous collective behavior and protest escalation. Using an interpretive qualitative design and an exploratory critical case study, the research treats photographs and videos as primary sociological evidence and analyzes them through a visual analytic framework grounded in visual sociology and visual criminology. The findings demonstrate that Kompas organized the protests into a linear escalation narrative from civil expression to chaos, prioritizing images of fire, smoke, and damaged architecture as signifiers. Early-phase visuals emphasize confrontation and synchronous crowd movement, shaping expectations of impending conflict, while later-phase images concentrate on symbolic destruction and the anonymity of the crowd, producing a collective blame effect that obscures individual responsibility. Post-escalation visuals highlight law enforcement, spatial control, and the restoration of order, legitimizing state authority through visual closure. At various stages, affective language amplified the fear and urgency while marginalizing the injustices felt by the protesters, thus translating political opposition into a securitized narrative of chaos. This study contributes to the study of protest and media by demonstrating that visuality is a constituent element of escalation dynamics and moral categorization, not simply a record of events. It also highlights the policy significance of critical visual literacy for evidence-based and humane protest governance in digital democracy.